Genophore Homologies Among Compatible Nocardiae - Clark, Josephine E. (1972)
Deoxyribonucleic acid (DNA) reassociation analyses were employed to determine the molecular relationships between recombinable nocardiae. Analysis of the compatibility system of Nocardia erythropolis Mat-Ce and Mat-cE mating strains demonstrated the existence of extensive homology under both exacting and nonexacting conditions. Labeled N. erythropolis Mat-cE DNA reassociated equally as well with the Mat-Ce test DNA as with its own filter-bound DNA. However, the Mat-cE DNA bound only ca. 60% of the Mat-Ce DNA, when the latter was the reference. The existence of unique nucleotide sequences is postulated on the basis of these results as well as of aberrant segregation patterns which have been observed in certain class types of recombinants. Reassociation data reveal that recombinants representing the inheritance of different portions of each of the parental genomes have inherited the unique portion from the Mat-Ce parent. N. restrictus AY-B-226 exhibited little relatedness (11 to 32%), and N. globerula ATCC 9356 only slightly more (21 to 42%), to either of these mating strains at either exacting or nonexacting temperatures of incubation.